TEMATISASI STUDI AL-QUR’AN - Abdurrahman (Fakultas Syariah - IAI Al-Qolam Malang, 2019)
The Qur'anic Studies is a study of various knowledge themes and theories that can illustrate the essence of the Qur'an. Because this knowledge is intended to introduce the Qur'an. It's just that the themes are as independent of each other and have no connection with each other, especially if studied by novice readers. According to the author's analysis, the actual themes in it are approaches from various dimensions; from the history, the mechanism of the text, the I'jaz system and the bayan method. These four dimensions are then made as major themes for the classification of all themes in the Qur'an Studies. These four major themes will be the first clue to finding the interrelation between themes, so that novice readers will get a holistic and comprehensive picture of the Qur'an.